왜 3x ^ 2 + 3 / x ^ 2 = 3 (x + 1 / x) ^ 2-6인가?

왜 3x ^ 2 + 3 / x ^ 2 = 3 (x + 1 / x) ^ 2-6인가?
Anonim

대답:

아래 증거를 보라.

설명:

이항식

# (a + b) ^ 2 = a ^ 2 + 2ab + b ^ 2 #

우리는 얻는다.

(x ^ 2 + 1 / x ^ 2) + 6-6 = 3 (x ^ 2 + 1 / x) ^ 2) #

대답:

아래를 봐주세요.

설명:

# 3x ^ 2 + 3 / x ^ 2 #

= # 3 (x ^ 2 + 1 / x ^ 2) #

= # 3 (x ^ 2 + 2 × x × 1 / x + (1 / x) ^ 2-2 - x × 1 / x) #

= # 3 ((x + 1 / x) ^ 2-2) #

= # 3 (x + 1 / x) ^ 2-6 #

# 3 (x + 1 / x) ^ 2 - 6 #

# 3 (x ^ 2 + 1 / x ^ 2 + 2) -6 #

브래킷을 열고, # 3x ^ 2 + 3 / x ^ 2 + 6-6 #

# 3x ^ 2 + 3 / x ^ 2 #